Kompetensi Guru Agama Kristen dalam Mendidik Tanpa Diskriminasi Mengajarkan Firman Tuhan dengan Objektivitas - Manti Matanari; Tiurma Berasa (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
Christian religious education plays a crucial role in shaping students' character and morals. Christian religious teachers are responsible for teaching God's Word with objectivity, without discrimination based on students' social, cultural, economic, ethnic backgrounds, or academic abilities. However, in practice, discrimination can still occur in various forms, both consciously and unconsciously. This study aims to analyze the competencies of Christian religious teachers in teaching God's Word objectively and to identify possible forms of discrimination in the learning process. Using a qualitative descriptive analysis method, this research examines religious education policies and teachers' experiences in the teaching process. The findings indicate that teachers with a deep understanding of theology, a neutral attitude in interpretation, discussion-based teaching methods, and high ethics and professionalism are better able to create an inclusive learning environment. To prevent discrimination, awareness and commitment from educators are needed so that the values of love and justice in Christian teachings can be realized in the learning process.